Steamer CITY OF TOPEKA at dock, Skagway, February 26, 1900. - Hegg, Eric A., 1867-1948 (1900)
Caption on image: "Steamer City of Topeka Feb 26 1900." Original image in Hegg Album 16, page 35. Original photograph by Eric A. Hegg 822; copied by Webster and Stevens 219.A.